Abundant expression and hemimethylation of C19MC in cell cultures from placenta-derived stromal cells - Flor, Inga; Helmke, Burkhard Maria (Biochemical and biophysical research communications, 2012)
MicroRNAs of the chromosome 19 microRNA cluster (C19MC) are known to be abundantly expressed in the placenta. Their genes are located on the long arm of chromosome 19 and seem to be part of a large imprinted region. Although the data available so far suggest important functions in the placenta, no data are available on their general expression patterns in cultures of placenta-derived mesenchymal stromal cells (PDMSC). Surprisingly, qRT-PCR on tissue cultures from first-trimester and term placenta mesenchymal stromal cells showed an abundant expression of the cluster members miR-517a-3p, miR-519a-3p, and miR-520c-3p. Accordingly, analyses of methylation patterns suggested that these cells had escaped methylation and epigenetic silencing, respectively, of the paternal allele. This was confirmed by the results of treatment of chorionic villous stromal cells by the demethylating agent 5-Aza-2′-deoxycytidine. Our results offer clear evidence that, in contrast to what is suggested in previous papers, members of C19MC are highly expressed in PDMSC indicating that their placenta-specific functions are not restricted to the trophoblast.